The Role of Educational Policy in Enhancing Norway's Global Competitiveness - Pustilnik, Iana (2025)
The aim of this thesis is to examine the role of educational policy in enhancing Norway's international competitiveness. In a global knowledge-based economy, developing human capital through education has become an essential criterion for a country's prosperity. The study considers Norway's performance in the Global Competitiveness Index (GCI) and the World Competitiveness Ranking (WCR), with a focus on the influence of education-related variables. A combination of secondary data analysis, reviews of education policies and reforms, and regression models is used to estimate the contribution of education expenditure, tertiary education attainment, skills development, and other education-related factors. The main findings confirm the link between investment in education and Norway's competitiveness. However, in highly developed economies such as Norway, the effect of additional investment is less pronounced and more closely linked to labour market adaptation and readiness for innovation. The thesis concludes that long-term strategic reforms in education strengthen Norway's global position and form the basis for future policies in a knowledge-based economy.